Handbook of Biodiversity Methods Survey, Evaluation and Monitoring - Hill, David; Fasham, Matthew; Tucker, Graham; Shewry, Michael; Shaw, Philip (Cambridge University Press, 2005)
Biodiversity is recognized to be of global importance, yet species and habitats continue to be under increasing pressure from human-induced influences. Environmental concerns are high on the political agenda, driving increased legislation to protect the natural environment. The starting point for much of this legislation is the requirement for a comprehensive biodiversity audit. This Handbook provides standard procedures which will enable practitioners to better monitor the condition of the biodiversity resource, resulting in improved data upon which to base future policy decisions and actions.